Annual Plan 1967-68 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1967)
Agricultural Production Training Centres Land Development Minor Irrigation Soil Conservation Development of Ayacuts Animal Husbandry Dairying and Milk Supply Forests Fisheries
Government of Andhra Pradesh Planning Department
Government of Andhra Pradesh Planning Department